Human Rights in Islamic Law and the Integration of Muslims in European Countries - Grynchak, Alla; Grynchak, Serhii (Problems of legality, 2023)
The steady growth of Muslim communities in European countries makes possible conflict situations due to the difference between Eastern and Western worldviews. The study of the European experience of finding possible ways to overcome intercultural crisis situations is relevant and expedient from the point of view of possible further implementation into national legislation. To achieve the goal, a set of methods was used: dialectical (for objectivity and comprehensive knowledge of the institution of human rights, taking into account various factors (in particular, religion), formal-legal method (for establishing the content of legal norms, analyzing the practice of their application), methods of analysis and synthesis (for the analysis of the constitutional legislation of foreign countries, which enshrines human rights and freedoms) and others. The comparative legal method was used as the leading one. The article compares Muslim and European approaches to the nature and content of human rights. The key characteristics of the legal status of a person, peculiar to Islamic law, are highlighted in the aspect of bringing such an understanding of human rights to the European environment. The constitutional-legal institution of human rights and freedoms in European states is based on the natural-law concept in the conditions of a liberal democracy and a secular state. Constitutional and legal norms on human rights in Muslim countries establish the inalienable influence of religion. The measures taken by the authorities of European countries are not effective enough. Only compromises, mutual respect for culture and preservation of religious foundations, and the use of primarily legal means of conflict resolution on both sides will help reduce tension and resolve disputes that arise between Muslims and European society. On the basis of the analysis and synthesis of constitutional and legal acts, scientific works, etc., possible ways of avoiding the problems of integration of Muslim minorities in Europe are suggested.